Living Donor Liver Transplantation Following Transcatheter Aortic Valve Implantation for Aortic Valvular Disease. (September 2020) - Kaliamoorthy, Ilankumaran; Rajakumar, Akila; Varghese, Joye; George, Susan; Rela, Mohamed
Over the last few decades, outcomes with living donor liver transplantation (LDLT) have improved significantly. This has resulted in patients who were denied liver transplantation previously, due to various comorbidities and high risk, now being considered for LDLT. This includes patients with severe valvular heart disease such as aortic stenosis. These patients require aortic valve replacement to help cope with significant perioperative hemodynamic changes. High-risk cardiac procedures like aortic valve replacement are associated with serious perioperative morbidity and mortality in patients with end-stage liver disease. Since the advent of transcatheter aortic valve implantation (TAVI) in 2002, there have been a few case reports of its successful use prior to deceased donor liver transplantation, but there is no literature on this procedure before LDLT. In this article, we report our experience with 2 patients, the first patient with infective endocarditis-induced acute aortic regurgitation and the second patient with bicuspid aortic stenosis who underwent uneventful TAVI followed by successful LDLT. In conclusion, with the increasing expertise and experience in this procedure, an increasing number of potential recipients, previously considered as high-risk transplant candidates, can now be offered liver transplantation by performing pretransplant TAVI.